การผลิตเยื่อแบบโซดาดัดแปรจากลำต้นข้าวโพด - วราพงษ์ โสพิน (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
Agricultural residue like corn stalks could be value added by being a potential fiber source for papermaking. However, pulping of corn stalks using soda process still resulted in high lignin content and low pulp yield when using high dosage of sodium hydroxide due to carbohydrate degradation. The soda process can be modified by adding anthraquinone (AQ) and/or methanol (MeOH) to improve pulp properties. Thus, the objective of this research was to study pulping of corn stalk using modified soda process by adding AQ and/or MeOH and compare pulp and handsheet properties of modified soda corn stalk pulp to those of conventional soda corn stalk pulp. It was found that modified soda pulping with AQ and/or MeOH could improve pulp yield and delignification as indicated by lower kappa number and higher brightness. Modified soda pulping also enhanced tensile and burst strength of handsheet. However tear resistance and opacity of handsheets were lower when compared to conventional soda pulping. These might be because AQ preserved carbohydrate while reacted with lignin, which led to lower lignin content and better fiber bonding. MeOH might enhance the impregnation of woodchips with sodium hydroxide, a cooking chemical. More lignin was then degraded and fiber bonding was improved. From the experiment, it was found that modified soda pulping from corn stalk not only provided better pulp yield but produced good pulp properties which is essential for high quality paper.